Urethroscopic Holmium: YAG Laser Ablation of Large Urethral Stone after Two-Stage Urethroplasty - Hosseini, Seyed Jalil; Mokhtarpour, Hooman; Bagher Tabrizi, Alireza; Hasanzadeh, Amin (Journal of Lasers in Medical Sciences, 2011)
Hairball in a urethral diverticulum has rarely been reported. These hairballs are usually formed in the diverticulum coated with a hair bearing epithelium and can lead to urinary obstruction or infection. Using laser is a safe way to ablate such stones.